Do the Unemployed Pay Lower Prices? A Reassessment of the Value of Unemployment Insurance. Issue 5 (26th October 2019) - Campos, Rodolfo G; Reggio, Iliana
Abstract: It is well known that transitions from employment to unemployment reduce consumption expenditure, but is this fall mainly driven by quantities or by prices? Using panel data on expenditure and quantities from the Spanish consumption survey we find that the unemployed pay prices that are, on average, 1.5% lower, and that this difference in prices accounts for roughly one sixth of the gap in consumption expenditure between the employed and the unemployed. The reduction in prices estimated with panel data is considerably lower than the existing estimates for the United States, which rely on cross-sectional comparisons. Based on our estimates, and using economic theory, we reassess the value of providing unemployment insurance and show how the social value of providing unemployment insurance can be decomposed into a consumption-smoothing component and a component that depends on prices.